Avaliação da política de inclusão escolar em um município na perspectiva de professores - Santos, Vivian (Universidade Federal de São Carlos, 2020)
This study is part of a bigger multimethod project that had the objective of analyzing the school inclusion policy within a city from São Paulo State (Brazil) using the Policy Cycle Approach (PCA). This research focused specifically in the teacher’s perspectives. In order to do so, three studies were elaborated. The first one focused on the context of international and local influence, realizing an integrative literature review and individual interviews with former staff members of the local education department. The second study investigated the context of text production, analyzing official documents within national (94 texts) and local (26 texts) levels. The third study analyzed the context of practice with 53 teachers from regular classrooms and 8 specialized teachers through: 1) individual and structured interviews, and 2) focus groups. Data about the context of influence highlighted how multilateral agencies influence policy guidelines about special education in Brazil by means of conferences and declarations. The local context analysis showed that the city policies followed the national movement adhering the national policy with strong presence of the third sector specialized institutions. In the context of text production analysis within the national sphere, four historic periods stood out: a) 2003-2006: starting the speech about schooling of students with special needs; b) 2007-2010: radicalism and confrontation tone which was softened along the period; c) 2011-2016: confrontation between the philanthropic institutions movement and the private education sector; and, d) 2016-2019: polarization between reviewing or not reviewing the national policy of special education in Brazil. The context of text production in the local scope showed three important groups of documents that aimed: a) To regulate the Special Educational Service within regular schools; b) To regulate the cooperation financial agreement with the private specialized institutions; c) To elaborate the Municipality Plan of Education and its monitoring reports. The data showed that the city studied firstly adhered to the national policy, but over the years there, translations and interpretations of their own started being used. The context of practice, analyzed through contextual dimensions with its own indicators, evidenced as the main challenges: demand for teacher training within special education field and lack of workload to collaborative planning between regular teachers and special education teachers. This reality resulted in difficulties within educational practices and the learning evaluations of students with special needs. The indicators about self-evaluation, degree of knowledge and training needs highlighted problems associated with understanding the special education policy and practice with students with special needs. Special Education teachers tended to give better evaluation to the policy when compared with regular teachers, this result can be explained by their qualification being mostly for the topic and, mainly, by the differences in their work conditions and the lack of support to the regular classrooms. Suggestions that the evaluation of the special education policy can yield better indicators stem from the elaboration of programs for continuing education, changes within the systematic support of the special education teacher with emphasis in the support directed to regular classroom teachers, and material investment to improve learning spaces for students with special needs. It is expected that this study adds to the enhancement of research tools and methodologies to evaluate the Brazilian school inclusion policy and to improve studies about educational policies in Brazil.
Teachers perspectives about the evaluation of the school Inclusion policy in a brazilian city
Keywords: Educação Especial; Política de inclusão escolar; Abordagem do ciclo de políticas; Special Education; Scholar inclusion policy; Policy cycle approach; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO